Nilai-Nilai Anti Korupsi dalam Buku Teks Pendidikan Agama Islam dan Budi Pekerti Sekolah Menengah Atas - Aris Munandar; Oki Dermawan (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
In tackling corruption in Indonesia there needs to be concrete preventive efforts, one of these efforts is through the education sector. Investing in anti-corruption values carried out consistently and continuously will foster students' personality attitudes, this can be done by integrating these values into a subject, one of the subjects that focus on the growth and development of student attitudes is the subject of Islamic education and character. This type of research is Library Research. The documentation technique is used in collecting data. Content analysis is applied in analyzing data that has been collected. As well as the deductive thinking patterns used in this study. The objects in this study are Islamic education textbooks and character published by the Ministry of Education and Culture of the Republic of Indonesia in grade 10, 11, and 12. The results showed that all anti-corruption values recommended by the Ministry of Education and Culture were sufficiently implicit in implicit Islamic textbooks in Islamic education and high school character traits. The form of disclosure of anti-corruption values is reflected through the subject of wetting, expressions, description of a story, forms of events that occur in the environment everyday, in the form of sentences, verses of the Al-Qur’an and the Hadits of the Prophet Muhammad, as well as images contains messages from a material